PENERAPAN PERTANIAN CERDAS BERBASIS INTERNET OF THINGS DAN AGROGEOFISIKA DI MADRASAH ALIYAH ITTAQOLLAH AMBON - Bahri, Samsul; Jaya, Gede Wiratma; Zulfiah, Zulfiah (Universitas Mataram, 2026)
Food security requires transformation of the agricultural sector through the application of technology. This article discusses a community service program aimed at addressing water scarcity and low interest in agriculture among young people at Ittaqollah Islamic High School in Ambon. The method used was community development with an interdisciplinary approach, combining geophysics for water exploration and Internet of Things (IoT) technology for smart irrigation. The activity began with subsurface mapping using geoelectric resistivity, which revealed a groundwater depth of >52 meters. This finding became the basis for implementing a rainwater harvesting solution installed on the school's roof. Next, an automatic irrigation system based on an ESP32 microcontroller was built and installed, integrated with a soil moisture sensor and controllable via smartphone. The program also included outreach and practical training for students and teachers. The results showed that the irrigation system operated optimally in both automatic and manual modes. This program demonstrates that the integration of geophysics and IoT can create sustainable solutions for water security, improve irrigation efficiency, and empower young people as future agricultural actors.